Evaluation of ultra-high-performance concrete columns at high temperatures after 180 days of curing (2023)
Ultra-high-performance concrete (UHPC) is a material that has high compactness, low porosity, and high mechanical strength, with especially high tensile strength. Due to these characteristics, the behavior of the material when exposed to high temperatures is debatable. The high amount of fibers in the mixture, which makes UHPC present a high tensile strength, is seen as one of the arguments for the good performance of the material when exposed to high temperatures. The objective of this study was to evaluate the behaviors of ultra-high-performance concrete columns with hybrid steel and polypropylene fibers and no loose reinforcements when subjected to elevated temperatures after 180 days of curing. The exposure of concrete with a low age, less than 90 days, to high temperatures results in greater damage to the concrete due to spalling, and because of this, this study sought to evaluate the UHPC with a higher age. Two columns were manufactured with a cross-section of 250 mm × 250 mm and a height of 2800 mm. A heating regime followed the heating curve of standard ISO 834-1. The physical characteristics of the samples were evaluated during and after exposure to high temperatures with measurements of the decreases in the cross-section and surface aspect. Effects on the compressive strength, modulus of elasticity, and apparent density were evaluated with cylindrical test bodies of 100 mm in diameter and 200 mm in height. These samples were cured for 180 days, subjected to the same heating regime, and evaluated after cooling. The results showed an increase in the compressive strength with an increasing temperature up to a factor of 30% at a temperature of 400 °C. The modulus of elasticity and apparent density decreased gradually as the temperature increased, with maximum decreases of 29% and 6%, respectively. Throughout heating, audible cracks were heard from the columns because of spalling. The spalling frequency peaked at an oven temperature of 600 °C, and testing was suspended at 78 min after the complete rupture of a column section. On average, 46.5% of the column cross-sections suffered from spalling.